Problems of conversions wooden sacred architecture of Lemko temples after 1947 - Uścinowicz, Jerzy (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
This paper presents selected examples of interconfessional conversions of lemko temples, after "Vistula Operation" 1947 in Poland. It also shows the process of transformation of spatial and functional structures as well as iconography of the temples, implemented throughout adaptation. It covers problems in architectural conservation as well as essential ideological aspects of symbolical and liturgical nature.